TINGKAT PENGETAHUAN GURU PJOK SMP SE-KABUPATEN MOROWALI UTARA, SULAWESI TENGAH TENTANG PENANGANAN DINI SAAT CEDERA - Cahyo Wibowo; Dennys Christovel; Rinaldy Manantuada; Yahya Eko Nopiyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
When doing sports can not be separated from the name injury. Most sports injuries occur in schools. Therefore, sports teachers play an essential role in handling injuries in schools. The purpose of this study was to find out how high the level of knowledge about early injury management using the PRICES (Protection, Rest, Ice, Compression, Elevation, Support) method of PJOK teachers at junior high schools in North Morowali Regency, Central Sulawesi. This type of research is descriptive and quantitative. This research uses the survey method, and in the process of collecting data using a questionnaire technique. The population in this study were PJOK junior high school teachers in North Morowali Regency, Central Sulawesi, amounting to 56 people. Sampling in this study using total sampling. The collected data is then analyzed using descriptive techniques with percentages. The results of this study show the level of knowledge of PJOK teachers of junior high school teachers in North Morowali Regency is in the high category. However, in implementation, it is seen that the factors of applying, analyzing, and evaluating the percentage are still lacking.